REPLICATION OF HIV-1 ENVELOPE PROTEIN CYTOPLASMIC DOMAIN VARIANTS IN PERMISSIVE AND RESTRICTIVE CELLS - Staubus, August O. (Virology, 2019)
Wild type (WT) HIV-1 envelope (Env) protein cytoplasmic tails (CTs) appear to be composed of membrane-proximal, N-terminal unstructured regions, and three C-terminal amphipathic helices. Previous studies have shown that WT and CT-deleted (ΔCT) Env proteins are incorporated into virus particles via different mechanisms. WT Env proteins traffic to cell plasma membranes (PMs), are rapidly internalized, recycle to PMs, and are incorporated into virions in permissive and restrictive cells in a Gag matrix (MA) protein-dependent fashion. In contrast, previously described ΔCT proteins do not appear to be internalized after their arrival to PMs, and do not require MA, but are only incorporated into virions in permissive cell lines. We have analyzed a new set of HIV-1 CT variants with respect to their replication in permissive and restrictive cells. Our results provide novel details as to how CT elements regulate HIV-1 Env protein function.